O presbítero católico: identidade, metamorfose e emancipação - Santos, Jésus Benedito dos (2009)
The fundamental aim of the present research is to examine the question of metamorphoses and emancipations in Catholic Presbyter s identity in Modern times. It takes for basis the concept of identity proposed by the Social Psychologist Antonio da Costa Ciampa as well as the Social Philosopher Jurgen Habermas theories. To attain this purpose, it becomes indispensable to undertake that the constriction of the of the identity of the catholic presbyter cannot be shaped without the ties of sociability, what has to be understood as an inter-subjective force that creates a sense of pertaining to the society; to accept that modern society is especially guided by post-conventional postulates whose conflicts are not essentially regulated by the religion or by the tradition, prevailing systemic interests and not the general or universal ethic principles; that in the course of the Catholic Church history, the presbiteral identity has already suffered many transformations, according to conjunctural-historic necessities; that the exercise of greater personal autonomy by the presbyter leads to greater self realization, liberty of choice, personal responsibility and the consciousness of a leading life; that nowadays, at the same time the presbyter feels himself as the security that the Catholic Church mastership and the society assured him and feels himself without definition, without limits, without content or purpose, having to build a complex identity. The research is based on the following procedures: in a first time, a bibliographical survey that seeks combine conceptions on identity proposed by the Catholic Church mastership, departing from the Second Vatican Council and also a research and reflection on presbiteral identity proposed by catholic theologians, psychologists and catholic seminary educators, problematizing with theories proposed by the Social psychologists Antonio da Costa Ciampa, as well as the theories proposed by the Social Philosopher Jurgen Habermas. In a second part, it shows an analysis of four presbyters lives trying to show each of them is trying to build this presbiteral identity in Modern times